(untitled) (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The purpose of this study was to determine whether shuttle sprint training helps basketball players become more agile. A one-group pretest-posttest design experiment was the research method used in this study. Shuttle running was used to assess the agility of the research participants before and after being given treatment. Using SPSS 24.0, data analysis was performed using t-tests, homogeneity tests, and normality tests. The agility of basketball players increased significantly, as evidenced by their average pretest score of 11.4 and posttest score of 10.7. The t-test produced a calculated t of 4.135 > t table 2.447 with a significance of 0.005 (<0.05), indicating that the agility of basketball players was significantly affected by shuttle sprint training. Consequently, shuttle sprint training is a useful technique for improving agility skills in both daily physical activities and competitive sports.